'In America è vietato essere brutte': advertising American beauty in the Italian women's magazine Annabella, 1945–1965. Issue 1 (22nd February 2017) - Harris, Jessica L.
Abstract : This article examines how the American conception of female beauty introduced new and distinct understandings of beauty and femininity to postwar Italy. In analysing beauty product advertisements from one of the most popular women's magazines of the period, Annabella, the article articulates the components of the American beauty ideal and illustrates how these notions broke with previous Italian ideas of beauty. Moreover, the article also examines how this new ideal promoted democratic consumer capitalist values – freedom of choice, individualism, and affluence – which had an important political and cultural significance in Italy's Cold War struggle. In light of this struggle and the country's postwar redevelopment, the American beauty ideal sought to influence the women who read Annabella and the way in which they fashioned and identified themselves – as the Italian 'Mrs Consumer.' Italian Summary: Questo articolo esamina come la concezione americana di bellezza femminile abbia introdotto nuovi e distinti significati di bellezza e di femminilità in Italia nei primi decenni del secondo dopoguerra. Attraverso l'analisi della pubblicità dei prodotti di bellezza apparsa su una delle più popolari riviste per donne del periodo, Annabella, l'articolo definisce le componenti della 'bellezza ideale americana' e chiarisce come queste componenti abbiano introdotto radicali elementi di discontinuità con le precedenti idee italiane di bellezza. Inoltre, l'articolo esamina come questo nuovo ideale abbia incentivato quei valori della democrazia capitalista e consumista – la libertà di scelta, l'individualismo, la ricchezza materiale – che ebbero un significato politico e culturale importante negli anni della guerra fredda. Nel contesto di questa lotta e della ricostruzione e dello sviluppo del paese nel dopoguerra, la 'bellezza ideale americana' tentò di influenzare le lettrici di Annabella e il modo in cui esse si formavano e si identificavano – creando la 'Mrs Consumer' italiana.